Прогнозування розвитку державного резерву в довгостроковому періоді - Ващенко, Валентин Васильович (НУБіП України, 2020)
Дисертація на здобуття наукового ступеня кандидата економічних наук зі спеціальності 08.00.03 «Економіка та управління національним господарством». Національний університет біоресурсів і природокористування України. Київ, 2020. На підставі результатів дослідження чітко обґрунтовано поняття «прогнозування» у поєднанні з авторським тлумаченням державного резерву, що дає підстави стверджувати про правильну обрану архітектоніку дослідження та необхідність комплексного забезпечення і раціонального поєднання всіх ланок структури управління державного резерву з урахуванням передового світового та європейського досвіду. У процесі детального аналізу фінансових показників удосконалення використання загального фонду Державного бюджету України зроблено висновок, що за рахунок модернізації, яку провели підприємства –відповідальні зберігачі матеріальних цінностей державного резерву, підвищеноефективність діяльності Держрезерву України. У роботі висвітлено сутність прогнозування розвитку державного резерву як комплексу умов, необхідних для мінімізації внутрішніх і зовнішніх загроз розвитку держави та розроблено модель створення мінімальних запасів нафти і нафтопродуктів в Україні як одного із важливих елементів енергетичної незалежності країни, що передбачає формування мінімальних запасів нафти і нафтопродуктів відповідно до вимог Директиви Ради 2009/119/ЄC. Застосовано прогнозне моделювання та розроблено п’ять варіантів зведених витрат на створення і підтримку мінімальних запасів сирої нафти та нафтопродуктів в Україні та подано форми і методи реалізації представленої моделі.
Thesis for a Candidate Degree in Economics in specialty 08.00.03 «Economics and Management of National Economy». National University of Life and Environmental Science of Ukraine. Kyiv, 2020. Based on the results of the study, the concept of «forecasting» is clearly substantiated in combination with the author's interpretation of the state reserve, which gives grounds to assert about the correctly chosen architectonics of the study, the need for comprehensive support and rational combination of all links in the management structure of the state reserve, taking into account the best world and European experience. In the process of a detailed analysis of financial indicators of improving the use of the general fund of the State Budget of Ukraine, it was concluded that due to the modernization carried out by enterprises – responsible custodians of the material assets of the state reserve, the efficiency of the State Reserve of Ukraine has increased. The paper highlights the essence of forecasting the development of the state reserve, as a set of conditions necessary to minimize internal and external threats to the development of the state, and developed a model for the creation of minimum stocks of crude oil and oil products in Ukraine as one of the important elements of the country's energy independence, which provides for the formation of minimum reserves of oil and oil products in accordance with the requirements Directive 2009/119/EU. The dissertation examines the forecasting and methodological foundations of the development of the state reserve in the long term. Predictive modeling was applied and five variants of the reduced costs for the creation and maintenance of minimum stocks of crude oil and oil products in Ukraine were developed, the forms and methods of implementation of the presented model are presented, namely: option 1 – Basic (all costs are covered over 5 years by the budget (increase); option 2 – similar to option 1 (the difference is that an investment tariff was applied for storage for 8 years to reimburse investments in the storage capacity of the storage facility, an increased investment rate must be paid over the next 5 years); option 3 –Basic, (the difference is 20 % participation of commercial firms in the volume of creation of the minimum reserves of crude oil and petroleum products, storage is paid by the Agency at basic tariffs); option 4 – Basic, (the difference is the removal of excise tax and VAT on the share of excise tax); option 5 – Basic, (the difference is the removal of excise and VAT on the share of excise tax, 20 % of the participation of commercial firms in the creation of the minimum reserves of crude oil and petroleum products). Possible sources of financing of the reduced costs of and maintaining minimum reserves of crude oil and petroleum products in Ukraine, in order to prevent dangerous phenomena and events, as well as to overcome their consequences. The model for the formation and preparation of minimum reserves of crude oil and petroleum products in Ukraine has been introduced, as the source: the structure of minimum stocks of crude oil and oil products in the general procedure for consumption until the end of the Directive, and by the minds, by the meaning of Regulation (EU) № 1099/2008; allocation of state reserves and stocks, so that subordinates of the state are responsible for supplying the market for crude oil and oil products; the central body, which realizes the state policy in the sphere of the formation and function of the minimum stocks of crude oil and oil products. The dissertation presents the forecast and methodical ambush of the development of the state reserve in the pre-construction period. The State Agency of the Reserve of Ukraine to enter the system of organs of the executive branch and is approved for the implementation of the state policy in the sphere of the state material reserve. A modern market is one of the leading elements of a larger folding system and a state-owned system, in which it is clearly interconnected with the mechanism of a rink mechanism, state-controlled institutes and a stand-alone state of the formation of a state-owned reservoir system. One of the fundamental departments of economic science is that food safety is energy efficient, because is smart enough to formulate national safety for any state.A wide range of fundamental principles in the development of the state is given to the public, so that Ukraine is made insignificantly due to the vigorous needs of oil and naphtha production. Protection of the left side of the current needs of the country in oil products is considered at the expense of supplies by oil traders. A whole negative factor can increase the destabilization of the situation in the country, problems with the supply of oil and oil to Ukraine. Ability to ensure the state is due to the factor and to ensure the minimum stocks of crude oil and oil products, the need for the establishment of such stocks is indicated until the Directive 2009/119/EU. Minimum stocks of crude oil and oil products allow for the growth of energy independence of the country and stabilization of the situation on the market of oil products in case of an interconnectedness or the supply of oil products in Ukraine. The issues of forecasting the development of the state reserve of Ukraine in the long term, which is a key link in the development of the state in modern conditions and the formation of a balance in the market for goods and paid services, the financial market and the labor market, are not fully covered. A number of problems related to the choice of indicators and methodological approaches to assessing and forecasting the level of the state reserve have not been resolved. In addition, the creation of minimal reserves of crude oil and petroleum products prevents the creation of artificial excitement in the petroleum product market. Even taking into account the fact that the model for creating minimum reserves of crude oil and oil products may provide for a slight increase in the price of oil products, this is a significant stabilizing factor for the growth of the country's economic potential. It was set up according to the forecast, which was revised according to the additional ARIMA model, but not depending on the seasonality, there is a tendency until a decisive change in the sale of diesel burners, which is expected to increase for 1 year, the tax rate will also change from the additional excise tax by 14–15 %.
Keywords: державний резерв; прогнозування; енергетична безпека; довгостроковий період; нафта; нафтопродукти; прогнозне моделювання; розвиток державного резерву; національна безпека; мінімальні запаси; перспектива; state reserve; forecasting; energy security; long-term period